(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In this paper author is describing concept to control or automate green traffic signal allotment time based on congestion available at road side using Canny Edge Detection Algorithm. To implement this technique we are uploading current traffic image to the application and application will extract edges from images and if there is more traffic then there will be more number of edges with white color and if uploaded image contains less traffic then it will have less number of white color edges. Empty edges will have black color with value 0. By counting number of non-zeroes white pixels we will have complete idea of available traffic and based on that we will allocate time to green signal. If less traffic is there then green signal time will be less otherwise green signal allocation time will be more.